2020
DOI: 10.15585/mmwr.mm6932a2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Marijuana Use During Pregnancy — Eight States, Pregnancy Risk Assessment Monitoring System, 2017

Abstract: TABLE. Maternal characteristics by marijuana use and cessation during pregnancy among women who used marijuana before pregnancyeight states,* Pregnancy Risk Assessment Monitoring System (PRAMS), 2017 Maternal characteristic Prepregnancy use weighted % (95% CI) (n = 765) † Marijuana use status during pregnancy weighted % (95% CI) aPR § (95% CI) Continuous use (n = 410) † Cease use (n = 355) † Total-41.2 (35.1-47.6) 58.8 (52.4-64.9)-Age group, yrs <20 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 8 publications
4
57
2
Order By: Relevance
“… 37 However, these earlier data predated the current opioid epidemic among pregnant people and the most recent sociopolitical changes in marijuana use. 7 , 15 , 20 , 38 , 39 As in the study by Rough et al, 37 self-reported opioid use was low in this population. Although one reason may be underreporting, another reason may be that SMARTT sites do not completely overlap with the regions most affected by the opioid epidemic or that individuals with greater opioid use may not enroll in studies such as SMARTT.…”
Section: Discussionsupporting
confidence: 57%
“… 37 However, these earlier data predated the current opioid epidemic among pregnant people and the most recent sociopolitical changes in marijuana use. 7 , 15 , 20 , 38 , 39 As in the study by Rough et al, 37 self-reported opioid use was low in this population. Although one reason may be underreporting, another reason may be that SMARTT sites do not completely overlap with the regions most affected by the opioid epidemic or that individuals with greater opioid use may not enroll in studies such as SMARTT.…”
Section: Discussionsupporting
confidence: 57%
“…Surveys of people in the United States who used cannabis during pregnancy indicate they do so to relieve stress, anxiety, chronic pain, nausea and vomiting. 51,52 However, our participants differed from those in previous survey studies because nearly half of the survey participants disclosed recreational cannabis use during pregnancy, which may reflect a difference in populations, greater social desirability bias in qualitative interviews or both.…”
Section: Discussionmentioning
confidence: 77%
“…Of note, cofounding factors such as race, social support, substance use, number of people in the household, alcohol problems with a parent, number of illnesses, and maternal depression were significant predictors for the composite score and other categories [23]. Other variables are that pregnant women were more likely to report using marijuana if they did not graduate high school, use tobacco or alcohol, and report a history of abuse or depression [24]. In addition, having a lower household income and being a single-parent were also additional co-variables seen across multiple studies [21] [23] [24].…”
Section: Cannabis and Fetal Outcomesmentioning
confidence: 96%
“…Other variables are that pregnant women were more likely to report using marijuana if they did not graduate high school, use tobacco or alcohol, and report a history of abuse or depression [24]. In addition, having a lower household income and being a single-parent were also additional co-variables seen across multiple studies [21] [23] [24].…”
Section: Cannabis and Fetal Outcomesmentioning
confidence: 99%